Law, Women, and Property in Contemporary Indonesia - Arskal Salim (Studia Islamika, 2014)
On 27-28 August, 2013, the School of Graduate Studies of UIN Syarif Hidayatullah Jakarta organised a two day conference on Law, Women and Property in Contemporary Indonesia. The conference was aimed to enhance understanding of recent socio-legal changes that affect Indonesian Muslim women and their access to property in the past few decades. In particular, it sought to investigate changing patterns in marriage and post-divorce payments, property transfers and the implications they are having upon women, children and legal processes in Indonesia.DOI: 10.15408/sdi.v21i1.884